Certain issues of legislative regulation of digitalization of healthcare in Kazakhstan - Tazhiyeva, M.N.; Mytalyapova, A.Sh. (Bulletin of the Karaganda University “Law Series”, 2025)
The aim of the work is to identify the imperfections of legal regulation that hinder the realization of the right to health care through the digital format of receiving medical services. To consider this topic, the authors studied the norms of national legislation affecting the processes of informatization of all spheres of the economy and digitalization of health care, in particular, through system analysis, comparative-legal and formallegal methods. As a theoretical basis, the authors studied legal scientific literature, documents of international organizations devoted to the subject of the study. In conclusion, the authors highlight the significant role of protection of personal medical data and principles of ethical application of artificial intelligence in the regulation of social relations in the field of digitalization of health care and the need to revise and harmoniously combine the norms of different legal acts regulating the digital development of health care.